Escalation of Community Legal Literacy in Resolving Land Disputes in Bumiaji Village, Batu City - Nuryasinta, Radhityas Kharisma; Puspitasari Wardoyo, Yohana (Universitas Negeri Semarang, 2024)
Land disputes are a significant issue in Bumiaji Village, Batu City, East Java, due to the community's low legal literacy and limited involvement of local stakeholders. Lack of understanding of formal legal procedures, the importance of land certification, and disharmony between customary and national laws have made it difficult to resolve land conflicts. This research aims to improve community legal literacy by considering the local context and strengthening the involvement of local stakeholders in land dispute resolution. The method used was Participatory Action Research (PAR), which actively involved communities and local stakeholders in problem identification, program design, and evaluation. The results showed that a locally-based approach that integrates customary and national laws was successful in improving community understanding of their legal rights and obligations, as well as encouraging participation in formal dispute resolution. In addition, the involvement of village officials, traditional leaders, and the National Land Agency in the dispute resolution process was able to create a more inclusive and equitable solution. The research concludes that legal literacy and synergy between local actors are key to resolving land disputes effectively and sustainably.